The Effectiveness of a Learning Program Based on STEAM In Computer Science for Gifted Students in Developing Scientific Reasoning - Yousif , Zainab Fattah; Al_Sindi , Naz Bader-Khan Abdullah (Journal of Ecohumanism, 2024)
The current research aimed to identify the effectiveness of the educational program based on STEAM in both scientific reasoning and innovative thinking of gifted students within the computer subject in their fifth preparatory grade.To achieve this goal, the null hypotheses have been adopted: There is no significant difference at the 0.05 level between the ranks of learners’ scores in the pre-test and post-test of scientific reasoning for gifted students who studied computer science according to the STEAM educational and learning program. The descriptive and quasi-experimental methods were adopted during the current research. The former was used for the purpose of building the educational program, while the latter was related to the application of the experiment, thereby demonstrating the effectiveness of implementing the program on a sample of gifted students in their fifth preparatory grade in computer science at the Mohobi Baghdad School, numbering (10) students in the academic year 2022-2023. The appropriate experimental design for the group, based on pre-test and post-test, has been adopted through the application of the Aloson scientific inference test.